Transformation of Islamic Religious Education Curriculum in Schools Facing the Challenges of Globalization and Multiculturalism - Noor Azida Batubara; Ahmad Dasuki (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze and identify the process of transforming the Islamic Religious Education curriculum in schools to face the challenges of globalization and multiculturalism. The transformation of the Islamic Religious Education curriculum in schools has become an urgent need in response to the challenges of globalization and multiculturalism, which increasingly affect the social and cultural life of society. Globalization, with its wide-ranging impacts on technology, economy, culture, and communication, influences how students understand the world and the values that evolve around them. On the other hand, multiculturalism, marked by the diversity of ethnicities, religions, and cultures in Indonesia, demands an education system that teaches tolerance, mutual respect, and the ability to live harmoniously amidst differences. The process of curriculum transformation in schools faces the challenges of globalization and multiculturalism. This method is chosen because it can provide a holistic understanding of the phenomena occurring within the context of education and how the curriculum is adapted to global and diverse developments in line with the changing times. Through an adaptive and inclusive curriculum transformation, Islamic Religious Education can play an important role in shaping a generation that is not only intellectually intelligent but also has strong character, based on religious moral values that can face the challenges of globalization and cultural diversity wisely. Thus, Islamic Religious Education will remain relevant in shaping individuals who are ready to contribute to peace and the progress of global society.